Performance of sowing/fertilizing machines in the settlement of upland rice crop - Silva, José Geraldo da; Kluthcouski, João; Stone, Luiz Fernando; Aidar, Homero; Oliveira, Itamar Pereira de; Ferreira, Evane (Pesquisa Agropecuaria Brasileira, 1998)
Upland rice (Oryza sativa L.) sowing with five sowing/fertilizing machines, EG 212-AS, PAR 3000, PST 2, MP 2000, and PP Solo models, working at three different displacement velocities, on a typic Haplustox soil, on two soil tillages (conventional and minimum tillage) was studied. The machines showed different performance in relation to operation velocity, sowing capacity and fuel consumption. Seed distribution, sowing depth and seed integrity were not affected by increasing machine operation velocity. There were less seeds per meter and sowing was deeper at minimum tillage. Fertilization depth was similar for all machines, independently of operation velocity and soil tillage. The worm gear fertilizer dosers were more suitable than the rosette or rotor ones. Rice sown with PST 2 yielded better than sown with EG 212-AS.